2014
DOI: 10.5194/acp-14-12839-2014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from a commercial cornfield (<i>Zea mays</i>) measured using the eddy covariance technique

Abstract: Abstract. Increases in observed atmospheric concentrations of the long-lived greenhouse gas nitrous oxide (N 2 O) have been well documented. However, information on eventrelated instantaneous emissions during fertilizer applications is lacking. With the development of fast-response N 2 O analyzers, the eddy covariance (EC) technique can be used to gather instantaneous measurements of N 2 O concentrations to quantify the exchange of nitrogen between the soil and atmosphere. The objectives of this study were to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 61 publications
(73 reference statements)
11
25
0
Order By: Relevance
“…This estimate comes from the first available long-term flux measurement datasets from managed crops and grassland measured with this technology (e.g. Huang et al, 2014; as well as unpublished datasets obtained by the authors; Merbold et al, 2014) and is also consistent with the detection limit reported during field deployments. Based on an intercomparison study carried out during the Integrated non-CO 2 Greenhouse gas Observing System (InGOS) project, Nemitz et al (2018) reported differences in standard deviations of flux values derived in the field were about twice the value reported by the manufacturers.…”
Section: Criteria For Analyser Selection and Minimum Annual Budgets Tsupporting
confidence: 70%
“…This estimate comes from the first available long-term flux measurement datasets from managed crops and grassland measured with this technology (e.g. Huang et al, 2014; as well as unpublished datasets obtained by the authors; Merbold et al, 2014) and is also consistent with the detection limit reported during field deployments. Based on an intercomparison study carried out during the Integrated non-CO 2 Greenhouse gas Observing System (InGOS) project, Nemitz et al (2018) reported differences in standard deviations of flux values derived in the field were about twice the value reported by the manufacturers.…”
Section: Criteria For Analyser Selection and Minimum Annual Budgets Tsupporting
confidence: 70%
“…Figures S16-S20 illustrate how the relationships between N 2 O and CO 2 emissions break down by individual chamber and by winter and growing season time periods. The emission rates observed in this study are comparable to literature values (Huang et al, 2014; Figure S14). However, we are interested in increasing our knowledge of local N 2 O emission behavior.…”
Section: Relationship Between N 2 O Emissions and Environmental Variasupporting
confidence: 91%
“…According to the methods introduced by Moncrieff et al (2004) and Ibrom et al (2007), the final N 2 O fluxes were corrected for this systematic underestimation by on average of 18%. The magnitude of the co-spectra correction agreed with the results reported by Huang et al (2014). The two periods we analyzed had different canopy conditions.…”
Section: Performance Of the Ec Measuring Systemsupporting
confidence: 88%
“…This piece of data was collected in the afternoon of 20 December 2014, when turbulence was well developed and N 2 O emissions were weak. Although the precision may have been even better by taking samples of standard gas, it was very close to the average estimates (0.31 ± 0.29 nmol mol −1 at 1 Hz) reported by previous studies that applied this kind of QCL analyzer (Kroon et al 2007;Neftel et al 2007Neftel et al , 2010Huang et al 2014;Rannik et al 2015).…”
Section: Performance Of the Ec Measuring Systemsupporting
confidence: 87%
See 1 more Smart Citation